Differences in audit pricing between voluntary and mandatory audits. Issue 2 (3rd August 2018) - Gandía, Juan L.; Huguet, David
Abstract : Purpose: Despite the extensive research on the determinants of audit pricing in both public and private settings, there is a lack of research about the differences in audit fees between voluntary audits and mandatory audits. The purpose of this paper is to address this gap. Design/methodology/approach: First, a theoretical framework is developed to justify differences in audit pricing between voluntary and mandatory audits. Next, using a sample of Spanish private small and medium enterprises (SMEs) running from 2009 to 2014, the authors empirically test whether the fees charged for voluntary audits differ from those charged for mandatory ones. The authors also examine whether the premium observed among large auditors is persistent in the SME setting, and whether this premium differs depending on whether the audits are voluntary or mandatory. Findings: Although a preliminary analysis does not report significant differences in pricing between voluntary and mandatory audits, additional analyses using samples restricted by company size show that voluntary audits are charged with a premium. The authors observe a premium related to large auditors, and find no significant differences in the audit pricing of Big 4 auditors depending on the mandatory/voluntary nature of the audit, but the premium associated with Middle-Tier auditors disappears in the voluntary setting. Originality/value: This paper contributes to the previous literature by introducing the examination of differences in audit pricing between voluntary and mandatory audits. As far as the authors know, this is the first study to examine the differences in audit pricing between voluntary and mandatory audits. It also elaborates on studies on audit pricing in SMEs. Abstract : Objetivo: A pesar de la extensa investigación sobre los determinantes de los honorarios de auditoría tanto en el entorno de las empresas cotizadas como de las no cotizadas, existe poca investigación sobre las diferencias en los honorarios entre las auditorías voluntarias y las obligatorias. El presente estudio aborda esta carencia. Diseño/metodología/enfoque: En primer lugar, se desarrolla un marco teórico que trata de justificar diferencias en el precio de la auditoría entre auditorías voluntarias y obligatorias. Después, usando una muestra de pymes españolas no cotizadas para el período 2009–2014, testamos empíricamente si los honorarios cargados en las auditorías voluntarias difieren de los cargados en las auditorías obligatorias. Examinamos también si la prima observada entre los grandes auditores en el entorno de las pymes es persistente, y si esta prima difiere en función de si la auditoría es voluntaria u obligatoria. Resultados: Aunque el análisis preliminar no reporta diferencias significativas en el precio de la auditoría entre auditorías voluntarias y obligatorias, análisis adicionales usando muestras restringidas por el tamaño de las compañías muestran que las auditorías voluntarias soportan una prima con respecto a las obligatorias. Observamos también una prima relacionada con los auditores grandes y medianos, y no encontramos diferencias significativas en el precio de la auditoría para las Big 4 en función de la naturaleza obligatoria/voluntaria de la auditoría, mientras que la prima asociada con los auditores medianos desaparece en el entorno voluntario. Originalidad/Valor: El estudio contribuye a la literatura previa al introducir el análisis de las diferencias en el precio de la auditoría entre auditorías voluntarias y obligatorias. Hasta donde sabemos, éste es el primer estudio que examina las diferencias de precio entre ambos entornos. El estudio también extiende la literatura previa sobre los honorarios de auditoría en las pymes.